Small Lot Housing as a Means to Realise Compact Cities: The Case of Perth, Western Australia. Issue 1 (2nd January 2020) - Swapan, Mohammad Shahidul Hasan; Khan, Shahed; Mackenzie, Madison; Iftekhar, Md. Sayed
ABSTRACT: The means of achieving urban consolidation is extensively discussed in urban planning literature. However, it is not completely clear how consolidation goals could be facilitated by promoting homes on smaller lots. The paper addresses the dichotomy in Perth's housing market created by strong policy support for apartments and multi-occupancy dwellings whereas there is an overwhelming demand for larger block single-family residences. We interviewed local government planners and developers to explore their views on appropriate design codes, consumer preferences and the potential for trade-offs. Findings from this study could encourage relevant stakeholders to approach urban consolidation in a more realistic way.